Fillings And Late Holocene Palaeoenvironments Of The Palustrine Depressions Of The Lopé National Park, Middle Ogooué Valley In Gabon - Victory Nfoumou Obame; Norbert Ondo Zue Abaga; Makaya M’voubou (European Scientific Journal, ESJ, 2022)
This work is devoted to the study of fillings and late Holocene palaeoenvironments of two marshes located in the savannas of the northern part of Lopé National Park in Gabon. Sedimentological and geochemical analyzes associated with 14C dating were performed on the sedimentary deposits of Yao and Vitex marshes. The results obtained were compared with these of the sedimentary core of the Lopé 2 marsh, previously analysed. All of these data show that the active filling of these marshes was carried out synchronously. The small variation observed are linked to specific physical characters to each of the marshes. This filling began between 2300 and 2000 cal years BP in all of the marshes. It started at the beginning of the humid climatic phase which followed the climatic pejoration recognized throughout the area of Atlantic Central Africa between 2500 and 2000 years BP. During this humid climatic phase, the rains were abundant and regular and the depressions were filled with sediments which are very rich coarse detrital elements from the erosion of slopes. The marshes and its banks were covered with sparse vegetation. Subsequently the sediments gradually become depleted in coarse detrital materials and enriched with organic constituents. This evolution would indicate a gradual reduction in erosion linked to the densification of the vegetation cover on the slopes. It is mostly related to the development of vegetation in the marshy basins. This development of the vegetation and the conservation of the organic matter of the marshes are due to the perennial flooding of the palustrine depressions.